A ressurreição da carne como princípio de acolhida das pessoas enlutadas - Pires, Kauê Antonioli (2021)
This work deals with Christian Hope, the theological virtue by which Christians hope for a complete life after death. Death and its anthropological consequences affect all human beings. Christianity has an answer to this drama: the Paschal Mystery in Christ Jesus. One must, however, take into account anthropological issues that account for the whole man. Taking the human being as a given it becomes possible to find references in the understanding of the articles of faith on the Resurrection of the Body and on the Communion of Saints that the human person is not immersed in the pain of death, but is able to cultivate the hope of Life Everlasting in the heart of the Christian community. Finally, this work seeks to find the reason for Christian hope, which is not in the “here and now”, but which needs the present reality as a way of answering to Everlasting Life.